Developing new pharmacotherapies for autism. (10th August 2013) - Ecker, C.; Spooren, W.; Murphy, D.
Abstract: Developing new pharmacotherapies for autism spectrum disorder (ASD) is a challenge. ASD has a complex genetic architecture, several neurobiological phenotypes and multiple symptom domains. However, new opportunities are emerging that could lead to the development of 'targeted' and individualized pharmacological interventions. Here, first we review these important new insights into the aetiology and neurobiology of ASD with particular focus on (i) genetic variants mediating synaptic structure and functioning and (ii) differences in brain anatomy, chemistry and connectivity in this condition. The characterization of the genotypic and phenotypic differences underlying ASD might in the future be invaluable for stratifying the large range of different individuals on the autism spectrum into genetically and/or biologically homogeneous subgroups that might respond to similar targeted interventions. Secondly, we propose a strategic framework for the development of targeted pharmacotherapies for ASD, which comprises several different stages in which research findings are translated into clinical applications. The establishment of animal models and cellular assays is important for developing and testing new pharmacological targets before initiating large‐scale clinical trials. Finally, we present the European Autism Interventions – A Multicentre Study for Developing New Medications (EU‐AIMS) Initiative, which was set up in the context of the EU Innovative Medicines Initiative as the first European platform for integrated translational research in ASD. The EU‐AIMS Initiative consists of academic and industrial partners working in collaboration to deliver a more 'personalized' approach to diagnosing and treating ASD in the future.